2009
DOI: 10.1007/s10669-009-9241-5
|View full text |Cite
|
Sign up to set email alerts
|

Metal decontamination of tannery solid waste using Tagetes patula in association with saprobic and mycorrhizal fungi

Abstract: A greenhouse trial was conducted to investigate the role of mycorrhizal and resistant fungi on heavy metal phytoextraction from different concentrations of tannery solid waste amended soil (10, 20, 50, and 100%) by Tagetes patula. The four treatments included were, the control (C) without any inoculum, mycorrhizal (M) inoculated with strongly mycorrhizal roots of Cynodon dactylon, fungal (F) inoculated with Trichoderma pseudokoningii and the combined inoculation with both mycorrhizal and fungal inocula (M ? F)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Three healthy plants of Hemarthria compressa having uniform sizes were grown in each pot. The fungal inoculums (10 mL/pot) were applied after every two weeks by following Bareen and Nazir [33]. The metal analysis of paper sludge was carried out before the experiment was set up for each treatment.…”
Section: Experimental Setup and Designmentioning
confidence: 99%
“…Three healthy plants of Hemarthria compressa having uniform sizes were grown in each pot. The fungal inoculums (10 mL/pot) were applied after every two weeks by following Bareen and Nazir [33]. The metal analysis of paper sludge was carried out before the experiment was set up for each treatment.…”
Section: Experimental Setup and Designmentioning
confidence: 99%
“…Moreover, when PGPB was used to seed bacterization, plants show enhanced root and shoot length, biomass and biochemical parameters such as chlorophyll, carotenoid and protein content [49]. Otherwise excellent works on the remediation capabilities of T. patula provide no information on the impact of using bacterial strains during remediation, or their significance for these plants [31,32]. Our present findings indicate that as in the case of plant morphology, F. arundinacea did not show major changes in biomass yield following sediment treatment; however, the use of RP92 strain on soil without sediment had a promoting effect.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds may be variably excreted by the plant in response to altering environmental conditions and have been shown to have antimicrobial, insecticidal and nematicidal effects [29,30]. It has been reported that T. patula is a very effective plant in benzo[a]pyrene remediation and offers substantial potential for soil metal remediation [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The species is also used as a companion plant for the protection of crops against nematodes by virtue of the secretion of the chemical alpha-terthienyl from its root tissues (Liu et al 2011). This species has also been reported to have the potential for application in soil metal remediation (Bareen and Nazir 2010;Liu et al 2011). Cultivars of T. patula are widely grown for ornamental purposes, both as annual garden plants and for the production of cut flowers, and its popularity is due in part to the ease of cultivation .…”
Section: Introductionmentioning
confidence: 99%